OPTIMALISASI PEMBELAJARAN BERDIFERENSIASI MELALUI STRATEGI” TAKE AND GIVE GIAT SELAKSA, BRAVO” - Fitria, Fitria; Utami, Madya; Yuniarti, Yayuk; Trimurniyati, Pera; Yusnita, Ciya Nurma (JURNAL ILMIAH PENDAS: PRIMARY EDUCATION JOURNAL, 2024)
"The implementation of clinical supervision in the learning community "Take and give giat selaksa, Bravo" in the differentiated learning process aims to (1) improve the competence of teachers in compiling teaching modules that implement differentiated learning (2) optimize the implementation of differentiated learning for teachers. This Best Practice is implemented through several activities (1) clinical supervision, (2) sharing with colleagues in the learning community, (3) utilizing external learning resources, (4) joint practice in compiling teaching modules and implementing differentiated learning practices, and (5) sharing differentiated learning videos. The impact of clinical supervision in the learning community "Take and give giat selaksa, Bravo" in implementing differentiated learning includes (1) teachers competence in compiling teaching modules for differentiated learning increases (2) the differentiated learning process can improve in all classes. From the data analysis, it can be seen that implementing clinical supervision in the learning community was successful with most teachers achieving very good qualifications, indicating the effectiveness of this strategy in improving the quality of differentiated learning in this school.